STUDI PENGATUR TEGANGAN GENERATOR TIPE SCR - TOGAR TIMOTEUS GULTOM (JURNAL ILMIAH SIMANTEK, 2020)
In general the generator requires a constant output voltage. The load of the generator can be known every time a varied loadchange will result in the generator changing to keep it constant. Delivery control on generators using a method of fieldreinforcement control by an automatic voltage regulator system. This voltage reinforcement is equipped with a generatorrelay. AVR is a tool that can automatically adjust the voltage on a generator. This setting will work in the event of a loadchange in the generator output while the machine is operating with normal rotation. In this case it is expected that the voltageof the generator to remain in a constant state.